2006
DOI: 10.1007/s10549-006-9366-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting response to primary chemotherapy: gene expression profiling of paraffin-embedded core biopsy tissue

Abstract: Gene expression analysis on core biopsy samples is feasible and identifies candidate genes that correlate with pCR to primary chemotherapy. Gene expression in IBC differs significantly from noninflammatory breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 69 publications
(79 reference statements)
2
34
1
Order By: Relevance
“…In addition, it is a prediction tool in determining the benefit of chemotherapy in the adjuvant setting for both node negative and node positive patients [1,18]. However, the ability of this assay to predict the benefit of chemotherapy in the neoadjuvant setting remains controversial [7,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is a prediction tool in determining the benefit of chemotherapy in the adjuvant setting for both node negative and node positive patients [1,18]. However, the ability of this assay to predict the benefit of chemotherapy in the neoadjuvant setting remains controversial [7,14].…”
Section: Discussionmentioning
confidence: 99%
“…Literature on the topic varies according to the assay used. While some support the use of assays in this capacity [2,7,8,14,16,22,24], others question their validity in predicting response to NCT [20]. Few studies concentrate only on ER+ patients and the ability to predict NCT response in this subset [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…For clinical decision-making, the RS is divided into three risk groups: low (<18), intermediate (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) and high (RS ≥31). Numerous studies have demonstrated that ER-positive breast cancer patients with a low RS have a low risk of recurrence and derive low benefit from chemotherapy, and that ER-positive breast cancer patients with a high RS have a high risk of recurrence but do benefit from chemotherapy [71,[86][87][88][89].…”
Section: Mammaprint  70-gene Signaturementioning
confidence: 99%
“…One example is gene expression profiling (gep) of breast tumours. Gene expression profiling tests examine expression levels of prognosticallyrelevant genes to establish the likelihood of benefit from chemotherapy and the recurrence risk within 10 years for node-negative, estrogen receptor-positive patients [2][3][4][5][6][7] . The recurrence scores produced by gep tests classify patients into groups with poor or good prognosis: Patients with low scores have a low likelihood of recurrence and will likely derive littleto-no benefit from chemotherapy; those with high scores will have a higher likelihood of recurrence and will likely derive high benefit from adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%